Prevalence of Gram-negative bacteria and antibiotic resistance in intensive care unit in King Fahad Specialist Hospital, Kingdom of Saudi Arabia - Fahad Abdullah Mohammed Al-Awwad,; Talal Khatm alrasheedi,; Abdulaziz Marje alrashdi,; Musaad Ibrahim Saleh Altuwayjiri,; Saleh Falah Alharbi,; Fahad Fathy Alanazi,; Abdulaziz. Hazzaa Alnomesi,; Sultan Khaled Alharby,; Hameed M Alrashedi,; Abdulmajeed Abdullah Alawad,; Ahmed Abdelhadi,; Bothina Abdelaziz kora, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Backgroundand aim:The prevalence of gram-negative bacteria and antibiotic resistance in intensive care units is a significant concern in healthcare settings worldwide. Gram-negative bacteria pose a substantial threat to ICU patients due to their ability to cause healthcare-associated infections.So, we aimed to investigate the prevalence and distribution of MDR gram-negative bacteria in the ICU of King Fahad Specialist Hospital, their risk, and prognostic factors. Methods:1089 specimens were collected from the patients in the King Fahad Specialist Hospital in Buraydah (Qassim region) from 2020 to 2022. Results: 66% of cases resulted in death, with the majority of patients being over 70 years old (48%). The trachealaspirate was the most common sample type, followed by blood culture and urine. The prevalence of multi-drug resistance (MDR) was 37.6%, with 32.7% showing no resistance, and 26.8% producing ESBL enzymes. Males had a higher prevalence of MDR, ESBL, and ESBL (MDR) compared to females. K. pneumoniae, A. baumannii, P. aeruginosa, and E.coli were frequently detected, while P. vulgarise was rare. K.pneumoniae and A. baumannii were more prevalent in older age groups. Additionally, K. pneumoniae exhibited higher resistance rates than E. Coli across various antibiotics, with Ampicillin showing the highest resistance rate at 95.1%. Conclusion:K. pneumoniae, A. baumannii, P. aeruginous, and E.coli were the highly detected bacteria in ICU mainly in Tracheal aspirate. While P. valgaris was the least detected one.Ampicillin, followed by Piperacillin, Oxacillin, Cefuroxime, Cefotaxime, Ceftriaxone, Amoxycillin/ Clavulanic acid, Moxifloxacin, and Aztreonam had the highest resistance rates.